The relationship between dental wear and age at death in British archaeological human skeletal remains: A re-evaluation of the 'Brothwell chart'. (December 2022) - Mays, S.; Zakrzewski, S.; Field, S.
Highlights: Brothwell's (1963) dental wear chart is widely used in ageing adult human skeletons. This work aims to reassess the validity and potentially update the Brothwell chart. The study sample is British archaeological skeletons (N = 870). Miles-like methods are used to assess the relationship between molar wear and age. A revised wear vs age chart is produced to replace the Brothwell chart. Abstract: The chart relating molar wear to age published by Brothwell in 1963 is widely used to estimate age at death in archaeological adult human skeletal remains, especially in Britain, but also more widely. The chart was based on examination of juvenile and adult dentitions from Neolithic to Medieval periods from Britain, but few further details of materials and methods were given. The aim of this work is to re-assess the value of molar wear for estimating age at death for adult human remains in Britain and, if necessary, to provide an updated replacement for the Brothwell chart. 870 dentitions (juveniles with at least one permanent molar erupted and adults) were examined dating from the Neolithic period onward. The aim was to use a Miles-like method to assess the relationship between molar wear and age – i.e. to calibrate wear rates using juvenile dentitions and then, by extrapolating from this baseline, estimating age from wear in individuals with successively more worn dentitions. We validate some key assumptions of the method. Molar wear bears a consistent relationship to dental age in juveniles and does not appear to vary greatly from Neolithic to Medieval times, nor in the post-Medieval rural group studied. First and second molars appear to wear at similar rates, as do third molars except in dentitions where wear is very advanced. The estimated rate of molar wear is somewhat slower than that estimated by Brothwell. The results allow a chart to be presented that replaces Brothwell's (1963) chart, and permits age estimation from molar wear in British archaeological human remains dating from Neolithic to Medieval times and, tentatively, for rural post-Medieval remains. It is not applicable to post-Medieval remains from most urban contexts where dental wear is much reduced.